Kepemimpinan Transformasional Kepala Sekolah dalam Membangun Ekosistem Wawasan Kebangsaan di Era Digital (Studi Kasus di SDN 1 Munjuljaya Kabupaten Purwakarta) - Aries Rapelianto; Endang Komara; Teti Ratnawulan; Okke Rosmaladewi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Elementary education in the digital era faces challenges in the form of demands for digital literacy, the strengthening of national insight, limited infrastructure, and policies restricting the use of gadgets in schools. These conditions place school principals in a strategic position to manage learning so that it remains relevant and character oriented. This study aims to analyze the practice of principals’ transformational leadership in building an ecosystem of national insight in the digital era within the context of limited facilities and regulatory paradoxes. This study employed a qualitative approach with a case study design conducted at SDN 1 Munjuljaya, Purwakarta Regency. The research subjects consisted of the school principal and teachers. Data were collected through interviews, observations, and documentation studies. Data analysis was carried out using an interactive model involving data reduction, data display, and meaning-making, while data validity was ensured through source and technique triangulation. The results indicate that principals’ transformational leadership is manifested through the exemplification of Pancasila values, communication of a national vision aligned with digital developments, encouragement of instructional innovation, and personal support for teachers’ professional development. These leadership practices promote the integration of national insight and critical digital literacy into learning activities without dependence on students’ personal gadgets. The impacts are reflected in improved teacher competence, the formation of a collaborative school culture, and the development of students’ tolerant, fair, and critical attitudes in responding to information. Keywords: transformational leadership, school principal, national insight, critical digital literacy